TikTok as a Medium for Contextual Vocabulary Learning in EFL: Students' Perceptions and Learning Experiences - Rosa, Chindy Hanggara; Suhartatik, Suhartatik (UIBU, 2025)
This study explores how TikTok can be utilized as a tool for teaching contextual vocabulary in English as a Foreign Language (EFL) learning and examines students' perceptions of this approach. This descriptive qualitative study employed thematic analysis of interview data collected from twelve first-semester English Department students who were interviewed about their experiences learning vocabulary through TikTok content from “English With Rhys”. The findings reveal that TikTok serves as an effective alternative medium for vocabulary learning, offering accessibility, engagement, and authentic contextual examples. The twelve participants reported increased motivation due to the entertaining and accessible format, and demonstrated an improved understanding of vocabulary usage in authentic contexts. However, challenges include potential distractions from entertainment content and the need for additional strategies like note-taking and repetition for better retention. TikTok demonstrates significant potential as a supplementary tool for contextual vocabulary instruction, complementing rather than replacing formal classroom learning.​